Use of Digital Mind Maps in Technology Education: A Pilot Study with Pre-Service Science Teachers - Debbağ, Murat; Cukurbasi, Baris; Fidan, Mustafa; Fidan, Mustafa; Debbağ, Murat (Vilnius Univ, Inst Mathematics & Informatics, 2021)
This case study aims at ensuring preservice science teachers to acquire experience by creating paper-based mind maps (PB-MM) and digital mind maps (D-MM) in technology education and to reveal their opinions on these mind mapping techniques. A total of 32 preservice science teachers, enrolled in the undergraduate program of Science Teaching at a university in Turkey, participated in this study. During the first three weeks of the six-week study, participants created PB-MM for certain subjects in science education. For the rest of the weeks, they created D-MM by using Coggle. As data collection tool, a form, consisting of open-ended questions, was used in this study. The obtained results demonstrated that the participants generally reported positive opinions including that mind maps are beneficial and useful tools in reinforcing, assessing and visualizing learning in general, making lessons more entertaining as well as offering ease of use. It was also concluded that students can also use mind maps in teaching of other topics such as Vitamins, The Earth and the Universe and Systems in particular, as well as in events like meetings, presentations, brainstorming. Advantages of D-MM were listed as the possibility of adding multimedia material, ease of correction processes and the visual richness, while its disadvantage was listed as experiencing technical problems. PB-MM contribute to psychomotor development of students as well as learning by performing/experiencing. The difficulty in processes such as deleting, editing, etc. and in adding videos and images constitute the restrictions of PB-MM technique.
Keywords: Digital Mind Map; Interactive Learning Environment; Collaborative Learning; Teacher Education; Technology Education